Cell technologies in the treatment of rheumatic diseases - N. F. Soroka; M. P. Potapnev; N. A. Martusevich (Научно-практическая ревматология, 2019)
Rheumatic diseases are caused by chronic autoimmune processes that require long-term therapy, which leads to the formation of resistance to the drugs used. The search for new approaches to their treatment in recent years has been enriched with the use of cell therapy methods. They are considered in this review of the literature and include the transplantation of hematopoietic stem cells, mesenchymal stem (stromal) cells, the induction or administration of T-regulatory cells, tolerogenic dendritic cells. The paper discusses methods of obtaining cell products, their safety and clinical use in patients with systemic lupus erythematosus, systemic sclerosis, rheumatoid arthritis, and other rheumatic diseases, and treatment complications. Based on the analysis, the authors give the comparative characteristics of various types of tolerogenic cell therapy for rheumatic diseases and point out their advantages, disadvantages, and the specific features of clinical application.